Computer Simulation for the Effects of Optical Aberrations on Solar Images Using Karhunen-Loeve polynomials - Hassan, Raaid Noffi; Ali, Huda Shaker; Wadee, Wafaa Hikmat (Iraqi Journal of Science, 2021)
Numerical simulations were carried out to evaluate the effects of different aberrations modes on the performance of optical system, when observing and imaging the solar surface. Karhunen-Loeve aberrations modes were simulated as a wave front error in the aperture function of the optical system. To identify and apply the appropriate rectification that removes or reduces various types of aberration, their attribute must be firstly determined and quantitatively described. Wave aberration function is well suitable for this purpose because it fully characterizes the progressive effect of the optical system on the wave front passing through the aperture. The Karhunen-Loeve polynomials for circular aperture were used to describe wave front deviations and to predict the initial state of adaptive optics corrections. The results showed that increasing the aberration modes causes an increase in the blurring of the observed image. Also, we conclude that the optical phase error is increased significantly when aperture’s radii are increased.